Barriers to women's disclosure of and treatment for substance use during pregnancy: A qualitative study. Issue 6 (November 2022) - Oni, Helen Tosin; Drake, James Alfred; Dietze, Paul; Higgs, Peter; Islam, M Mofizul
Abstract: Introduction: The use of alcohol and or illicit drugs during pregnancy is a complex public health issue. There are many adverse short- and long-term health implications of substance use during pregnancy that can potentially affect the mother-foetal dyad. Although prevention and treatment options — such as counselling, pharmacotherapy, rehabilitation, support and case management and withdrawal management — are available, a range of barriers impedes women's ability to disclose their substance use, which limits access and engagement with available services. Objective: This research explored barriers women encountered in disclosing substance use and accessing substance use treatment in pregnancy. Methods: Participants were recruited from a longitudinal cohort study of people with a history of injecting drug use from metropolitan Melbourne. One-on-one in-depth interviews with 15 participants were conducted using a semi-structured interview guide. To be included in this study, participants must have reported a history of substance use during one or more of their pregnancies. Results: The fear of losing child custody associated with the involvement of the child protection services was one of the main barriers to disclosing substance use during pregnancy and accessing treatment and rehabilitation services. Other barriers including stigma and perceived limited treatment options impacted women in various ways. Conclusion: Pregnancy is an important time for women and offers opportunities for service providers to support women who are using substances. While not all barriers can be removed, careful consideration of individual cases and circumstances may help service providers to tailor interventions that are likely to be more successful.